Review of competitive neutrality in the medical indemnity insurance market : report - Rogers, Graham; Australia. Treasury (Canberra : Australian Government, 2005)
The Australian Government commissioned an independent review to examine the source and extent of competitive advantages in the medical indemnity insurance industry arising from Government assistance, to identify and evaluate options to redress any imbalance, in the context of its general policy aims of affordable and stable medical indemnity insurance.
Preliminaries and executive summary -- Introduction -- Current state of the medical indemnity industry -- Impact of individual assistance -- Premiums and pricing -- Assessment of competitive advantage -- Redressing the balance.
"March 2005"
Also available on the internet. Address as of 03/11/05: http://www.treasury.gov.au/contentitem.asp?NavId=002&ContentID=965
System requirements: Adobe Acrobat Reader required to view/print PDF files.
Keywords: Physicians -- Malpractice; Physicians -- Australia -- Insurance requirements; Physicians' malpractice insurance -- Australia; Malpractice insurance -- Australia; Medical personnel -- Malpractice -- Australia